Reexamining the inequality of opportunity in education in some European countries. Issue 7 (15th April 2020) - Lasso De La Vega, Casilda; Lekuona, Agurtzane; Orbe, Susan
ABSTRACT: This paper analyzes inequality of opportunity in education in 20 European countries. We aim to examine to what extent students' educational achievements are conditioned by circumstances such as their family background, school characteristics and peer effects, and by their own efforts. To that end, we propose a model that allows us to analyze the total effect of circumstances on overall education inequalities. Then, we propose a measure of inequality of opportunity that captures that effect. We find that, among the selected countries, Belgium, France, Germany, Switzerland and Luxembourg show the highest levels of inequality of opportunity, whereas Finland, Romania, Ireland, Spain and Norway get the lowest.